The link between genetic variation and variability in vaccine responses: a narrative review. Issue 2 (June 2022) - Zhang, Yingtian; Zhao, Mingzhe; Zhou, Wei; Chen, Luan; Li, Mo; Jiang, Bixuan; Zhao, Xianglong; Wu, Hao; Shen, Lu; Zhang, Na; Qin, Hengwei; Tang, Yuhao; et al.
Abstract : Abstract: Vaccines are one of the biggest successes in modern history and are particularly important in light of the multiple ongoing epidemics. Recently, vaccines have protected peoples' health and lives around the world during the coronavirus disease 2019 pandemic. Different types of vaccines have their own characteristics and advantages and are used in the context of different epidemics. Responses to vaccination are also different, and can include adverse reactions and absent responses. These individual differences are thought to be influenced by host genes. In this review, we first discuss vaccine types and characteristics. Second, we discuss different responses to vaccination, primarily focusing on the association between genetic variation and inter-individual differences.